Assessing the Need for a Specialist Service for People with Intellectual Disabilities and Mental Health Problems Living in Israel: A Qualitative Study - Sinai, Amanda; Werner, Shirli; Stawski, Mike (Frontiers in Pediatrics, 2013)
Background It is well established that people with intellectual disabilities are at higher risk of developing mental illnesses. This study aimed to assess the need for a specialized service for people (children and adults) with intellectual disabilities and mental health problems living in Israel. Methods Our research question was: Is there a need for a specialist mental health service for people with intellectual disabilities living in Israel and, if so, what type of service would be most appropriate? We conducted a qualitative study using semi-structured interviews with 14 major stakeholders to identify key themes in response to our research question. The data were coded and themes were identified. Results Participants were generally not satisfied with current mental health care for people with intellectual disabilities and there was a general agreement that services are in need of improvement. We identified three major themes from the data. These were: current services, future services and ways to facilitate change. Conclusions We hope that our findings will be instrumental in shaping the ongoing debate about the best form of delivery of services to this population in Israel. Specifically, we suggest the development of a more specialized system, with the formation of multidisciplinary regional assessment and treatment units in parallel with improved relevant training for all mental health workers and the possibility of referral to specialized teams in more complex cases.